TEXTUAL FUNCTION IN THE JAKARTA POST EDITORIALS - Novita S. C Naibaho; Zainuddin Zainuddin (State University of Medan, 2014)
ABSTRACT This research deals with Theme and Rheme in Editorials texts of The Jakarta Post newspaper. The aims are to find out the optional element dominates the structure of theme in the editorials of The Jakarta Post newspaper and to describe where the optional dominant element occurs. The research was conducted by using descriptive qualitative method. The data were collected from three different editions of The Jakarta Post editorials which is publish on January 2014. The findings indicate that conjunction was an element dominantly used in textual theme because there were so many compound clauses and there were two or more clauses in coordination relation or dependency on another. In interpersonal theme, adjunct was an element dominantly used that is means that a prepositional phrase has its own internal structure containing complement within it and preposition is put at first position of a clause which is called Theme. Conjunction and adjunct were dominantly used when the editors tells their argumentation, comment and their assessment of the news, because of the using of colloquialism or spoken language in editorials of the Jakarta Post newspaper. Keyword : Theme, Rheme, Editorial